LEGACY OF UTPALA DYANSTY IN KASHMIR WITH SPECIAL REFERENCE TO AVANTIVERMAN FROM (855-883 A.D) A HISTORICAL STUDY - Ahmad Lone, Shabir (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Most people consider Jammu and Kashmir to be heaven on earth. If there is heaven on earth, it is this, this, and this, according to the Farsi couplet (Amir Khusrau). The couplet encouraged numerous kings to exercise control over Kashmir. In the metrical chronicle known as Rajatarangni, dynasties in ancient Kashmir that dated from the time of the Mahabartha epic to the reign of Sangrama Deva are vividly portrayed. Of all the kings of ancient Kashmir, Avantivarman, who established the Utpalas dynasty in 1855 A.D., was the most magnificent. He didn't start any battles, not even to retake the areas that his forefathers had recently lost. In terms of prosperity, he ruled during the rippling times of peace and plenty, which coincided with Kashmir reaching its pinnacle around a quarter of a century into his rule. The people had never been happier than they were in his day, nor had they been for generations. Therefore, Avantivarman rule represents a very wonderful era in Kashmir's history. A new period in that nation's history began with Avantivarman taking control of events in the valley. His rule not only provided respite to Kashmir's suffering people, but it also significantly restored the Karkota's former luster, as will be seen. Avantivarman, a descendant of the Kalyapala family and the grandson of Utpalas, who had played a crucial role in the final years of the Karkota monarchy, was previously mentioned. Avantivarman has the traits of intellect and heart that allow him to be recognised as one of the valley's most capable kings, while not being by any means a member of some aristocratic and distinguished family. The study's goal is to explain and analyze Avantivarman legacy and reign during the Utpalas Dynasty in Jammu and Kashmir. It also highlights his contributions during his time in power there.